Social Justice and Counselling Psychology: Recommitment Through Action - Kennedy, Barbara A.; Arthur, Nancy (Canadian Journal of Counselling and Psychotherapy, 2014)
Historically, social justice has been one of the core values guiding the practice of counselling psychology. There are controversies surrounding the meaning of social justice and how it can be used to guide the roles and practices of counselling psychologists. The discussion here situates social justice as a primary value for professional identity. The article considers a definition of counselling psychology in Canada and whether or not it sufficiently supports a social justice orientation. The discussion focuses on the relationships between social and systemic influences on mental health. It also focuses on how counselling psychologists and counsellors could (a) expand their practices to address the conditions that have aversive effects, and (b) focus more on health promotion and well-being. The call for counselling psychologists and counsellors to position social justice centrally in their professional identity will require a fuller scope of practice to address social inequities and to help clients overcome barriers that persistently impact their mental health. Suggestions for recommitment to social justice are examined, with selected examples for practice, education, and research to illustrate how social justice can be strengthened through action.